Strategi Disdukcapil Kota Tanjungpinang dalam Optimalisasi Penggunaan Identitas Kependudukan Digital (IKD) pada Pelayanan Administrasi Kependudukan - Muhammad Razaq; Muhammad Hafiz; Mohammad Fais Wira Agusrianto; Nazaki Nazaki (Kajian Administrasi Publik dan ilmu Komunikasi, 2026)
This study is motivated by the acceleration of digital transformation in civil administration services, particularly the implementation of Digital Population Identity (IKD) as a technology-based public service innovation. Although it is designed to improve service accessibility and efficiency, the utilization of IKD has not yet been fully optimized by the community. This research aims to analyze the strategies employed by the Civil Registration and Population Administration Office (Disdukcapil) of Tanjungpinang City in optimizing the use of IKD in civil administration services. A qualitative research method with a descriptive approach was employed to obtain an in-depth understanding of the implementation strategies adopted by the institution. Data were collected through interviews, observations, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that Disdukcapil Tanjungpinang implements several key strategies, including community socialization and education, improvement of digital-based service quality, collaboration with various institutions, and strengthening the capacity of service officers in assisting IKD users. However, the implementation still faces several challenges, such as low digital literacy among some citizens, limited internet access, and resistance to digital service changes. This study concludes that optimizing IKD utilization requires synergy between institutional strategies and increased public awareness. The implications emphasize the importance of strengthening digital governance policies, improving information technology infrastructure, and implementing continuous digital literacy programs to ensure more effective and equitable use of IKD.